Iron and steel in art: corrosion, colorants, conservation - Garcia Alonso, Emma (Ge-conservacion, 2011)
Reseña del libro:Iron and steel in art: corrosion, colorants, conservation David A. Scott y Gerhard Eggert Publicado por Archetype Publications Ltd. London, 2009 196 páginas, 138 ilustraciones, 30 x 21,5 cm. ISBN: 978-1-904982-05-0